Conceptual model of public-private partnership in tourism - A. Tleuberdinova; A. Aldabergenova; D. Salauatova (Экономика: стратегия и практика, 2021)
The development of the tourism sector in Kazakhstan can be facilitated by the optimization of its management on the basis of public-private partnership, as one of the most effective forms of mobilizing the state and business to solve the problems of tourism development.The article provides a comprehensive analysis of the theoretical foundations of the mechanism of public-private partnership and the specifics of public-private partnership in tourism, in particular. Based on the analysis of foreign, Russian and domestic sources, a number of approaches to the formulation of the term «public-private partnership» were identified. The advantages of partnership for the state and business in the field of tourism are determined.The purpose of the study is theoretical review of the role and significance of public-private partnerships for the development of the tourism industry and the design of a conceptual model of public-private partnerships in tourism.The result of the research was the design of a conceptual model of public-private partnership for the tourism industry, which can serve as a theoretical and methodological basis for the implementation of a strategic course for the development of the tourism industry. The research results can be used in the development of state and regional programs for the development of the tourism industry.